Evaluation of the prognosis of acute subdural hematoma according to the density differences between gray and white matter - Li, Zean; Feng, Yan; Wang, Pengju; Han, Shuai; Zhang, Kang; Zhang, Chunyun; Lu, Shouyong; Lv, Chuanxiang; Zhu, Fulei; Bie, Li (Frontiers in Neurology, 2023)
Objective Acute subdural hematoma (ASDH) is a common neurological emergency, and its appearance on head computed tomographic (CT) imaging helps guide clinical treatment. To provide a basis for clinical decision-making, we analyzed that the density difference between gray and white matter of the CT image is associated with the prognosis of patients with ASDH. Methods We analyzed data of 194 patients who had ASDH as a result of closed craniocerebral injury between 2018 and 2021.The sample was subdivided into surgical and nonsurgical groups, and the nonsurgical group was further subdivided into “diffused [hematoma]” and “nondiffused” groups. The control group CT scans were normal. Software was used to quantitatively analyze the density of gray and white matter depicted in the CT images. Results Imaging evaluation showed that the median difference in density between the gray and white matter on the injured side was 4.12 HU (IQR, 3.91 – 4.22 HU; p < 0.001), the noninjured side was 4.07 HU (IQR, 3.90 – 4.19 HU; p < 0.001), which suggested that surgical intervention. The median density difference value of the gray and white matter on the injured side was 3.74 HU (IQR, 3.53 – 4.01 HU; p < 0.001) and that on the noninjured side was 3.71 HU (IQR, 3.69 – 3.73 HU; p < 0.001), the hematoma could diffuse in a short time. Conclusions Quantitative analysis of the density differences in gray and white matter of the CT images can be used to evaluate the clinical prognosis of patients with ASDH.